Increasing the bioactive space of peptide macrocycles by thioamide substitution - Verma, Hitesh (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
We show that substituting a single atom, O to S (amide to thioamide), in a peptide bond results in global restriction of the conformational flexibility in peptide macrocycles with minimal perturbation of the parent conformation. The van der Waals interactions between the C[double bond, length as m-dash]S group and the surrounding atoms are the major driving force in inducing the conformational restriction, resulting in well-defined structures of these cyclic peptides with static 3-D presentation of the pharmacophores. Utilizing this property of thioamides, we report the development of a superactive antagonist of pro-angiogenic αvβ3, αvβ5 and α5β1 integrins, which are responsible for cancer cell proliferation and survival. Using simple thio-scanning and spatial screening of a non-efficacious and conformationally flexible cyclic peptide, we could achieve a more than 10(5) fold enhancement in its efficacy in cellulo via a single O to S substitution. The developed peptide shows better efficacy in inhibiting the pro-angiogenic integrins than the drug candidate cilengitide, with a significantly enhanced serum half-life of 36 h compared to that of cilengitide (12 h). The long shelf-life, absence of non-specific toxicity and resistance to degradation of the thioamidated macrocyclic peptides in human serum suggest the promise of thioamides in markedly improving the affinity, efficacy and pharmacology of peptide macrocycles.